Prospective analysis of the agricultural trade relations between Peru and India from 2019 to 2023 before the free trade agreement. - Pantaleón Santa María, A.L. (2024)
The primary objective of this research was to analyze the agricultural trade relations between Peru and India from 2019 to 2023. A quantitative methodology was employed, with a descriptive scope and a non-experimental design, using data from SUNAT and INFOTRADE (PROMPERÚ). The results indicate that the trade intensity index (TII) of Peruvian agricultural exports to India declined by 40 % in 2020 and 41 % in 2021 but rebounded in 2022 and 2023 with increases of 132 % and 8 %, respectively, resulting in an average annual growth rate of 15 %. Likewise, agricultural imports from India increased by 55 % in 2020, dropped by 47 % in 2021, grew by 34 % in 2022, and declined by 13 % in 2023, with an average annual growth rate of 7 %. Among exported products, blueberries, which had no recorded exports in 2019, reached $ 1,58 million USD in 2023, accounting for 27,39 % of total exports. Powdered tara increased from $ 597 000 USD in 2019 to $ 960 000 USD in 2022 but declined by 79,79 % in 2023. It is concluded that, despite growth in certain products, logistical and tariff barriers continue to constrain bilateral trade. It is recommended to expedite negotiations for a free trade agreement and enhance trade infrastructure.